Target measurements influence on level crossing detection system safety determination. (March 2019) - Addabbo, Tommaso; Della Giovampaola, Cristian; Fort, Ada; Mugnaini, Marco; Pozzebon, Alessandro; Toccafondi, Alberto; Vignoli, Valerio
Highlights: It discusses the problem of safe level crossing under a wide variety of sensing aspects. It considers both the statistical and the physical sensing aspects of new technologies for railway applications. It presents both models and field data on a wide variety of cases. Abstract: The design of critical safety systems is usually approached through the investigation about the applicability of specific standards that can be applied in that specific field of interest. Even if very often this design strategy can be satisfactory to address the most part of common problems, sometimes a generalized approach may lead to tricky situations where some crucial aspects can be neglected. This risk is high when new technologies or advanced measurement systems are designed. The main reasons may lay in some hidden hazards related to the sensor physics or to the specific context. In this paper the authors discuss how the implementation of a peculiar system for level crossing monitoring (LC) based on a specific radar technology can be jeopardized if a limiting standard approach is followed. Moreover, a sharp analysis of the target to be detected is performed. Safety systems based on single or multi sensor architectures are analyzed discussing the advantages and pitfalls of the different designs in terms of system RAMS parameters. Considerations about measurement uncertainties due to the type and orientation of the specific item to be detected are presented on an empirical basis as well.